Hubungan Dukungan Keluarga terhadap Keikutsertaan Wanita Usia Subur pada Program KB di Puskesmas Sialang Buah Kab. Serdang Bedagai - Yesni Rosmawai Simanullang; Dewi Sartika Hutabarat; Adelina Sembiring (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Background: The Family Planning (FP) program aims to control population growth and improve the quality of family life. One of the factors influencing the participation of Women of Reproductive Age (WRA) in FP is family support, particularly from husbands. Data from the Sialang Buah Public Health Center show that the coverage of active FP participants in 2022 remained below the target, indicating the need for research on contributing factors, including family support. Objective: To determine the relationship between family support and the participation of WRA in the FP program at the Sialang Buah Public Health Center, Serdang Bedagai Regency. Methods: This study employed a cross-sectional design with a total sample of 55 WRA, selected using simple random sampling. The independent variable was family support, while the dependent variable was FP participation. Data were collected using a structured questionnaire and analyzed using the Chi-square test at α = 0.05. Results: Most respondents reported high family support (58.2%) and participated in FP (69.1%). Bivariate analysis revealed a significant relationship between family support and FP participation among WRA (p = 0.001), with respondents receiving high family support being more likely to participate in FP compared to those with low family support. Conclusion: Family support is significantly associated with WRA participation in the FP program at the Sialang Buah Public Health Center. It is recommended that healthcare providers enhance family involvement, especially that of husbands, in FP counseling to increase WRA participation.